Assesment of Ground Water Quality Near Animal Ferms in and Around Patiala - Singh, Piyush (My University, 2007)
Water available below the ground surface is termed as ground water and this occurs as surface water (rain/melting snow) infilters into the ground surface and percolate deep into the ground and is stored as ground water. This recharge of ground water also occurs from excess irrigation, seepage from canals, leakages from reservoirs etc. The ground water held by geological formations is not static but is slowly moving in the lateral direction to some point of escape. Surface water is majorly used for domestic and industrial activities whereas in India the demand for irrigation is met by ground water. Ground water is generally purer than surface water. Yet it may contain some natural impurities or contaminants, even with no human activity or pollution. Natural contaminants can come from many conditions in the watershed or in the ground. Water moving through underground rocks and soils may pick up magnesium, calcium and chlorides. Some ground water naturally contains dissolved elements such as arsenic, boron, selenium, or radon, a gas formed by the natural breakdown of radioactive uranium in soil.
Keywords: Ground Water Quality; Animal Ferms; Ground Water Contamination; Livestock Production